2019
DOI: 10.1155/2019/2413919
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Electrical Stimulation Alleviates Headache through CGRP/COX-2/TRPV1/TRPA1 Signaling Pathways in a Nitroglycerin-Induced Migraine Rat Model

Abstract: The study aimed to investigate effect of auricular electrical stimulation (ES) on migraine. Migraine was induced in rats by intraperitoneal administration of nitroglycerin (NTG, 10 mg/kg) three times. Auricular ES pretreatment was performed for five consecutive days. Migraine behaviors were observed by a video recording. Auricular ES pretreatment could reverse the decrease of the total time spent on exploratory (2619.0 ± 113.0 s vs 1581.7 ± 217.6 s, p=0.0029) and locomotor behaviors (271.3 ± 21.4 s vs 114.3 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Two members of the TRP superfamily are TRPA1 and TRPV1 channels, and they are also activated by OS [8,13]. The involvements of TRPA1 and TRPV1 on the GTNmediated migraine and pain models were recently reported [55][56][57]. Within the OS-dependent-activated TRP channels, TRPM2 is first discovered channel [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Two members of the TRP superfamily are TRPA1 and TRPV1 channels, and they are also activated by OS [8,13]. The involvements of TRPA1 and TRPV1 on the GTNmediated migraine and pain models were recently reported [55][56][57]. Within the OS-dependent-activated TRP channels, TRPM2 is first discovered channel [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Within the NTG model, TRPA1 activation is probably caused by either nitric oxide or reactive oxygen species and inflammatory mediators [23,[38][39][40], all of which increase after the NTG challenge [17,[41][42][43][44]. Accordingly, previous studies reported increased TRPA1 gene expression and immunoreactivity in the TGs of NTG-treated rats [16,45].…”
Section: Trpa1 Antagonism In Migraine-like Painmentioning
confidence: 95%
“…Although animals are not verbal, recent studies have considered NTG-induced animal models as clinically relevant due to the translational ability of behavioural endpoints [ 12 , 21 ]. Our previous studies showed that NTG-induced nociceptive behaviours in rats with migraine headache included reduced exploratory and locomotor behaviours and increased resting behaviour [ 33 , 34 ]. The aforementioned nociceptive behaviours in rodents mimicked those experienced by people with migraine, who generally present with reduced involvement in routine physical activity and decreased interest in exploring new surroundings or objects during an acute migraine attack episode [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that NTG-induced nociceptive behaviours in rats with migraine headache included reduced exploratory and locomotor behaviours and increased resting behaviour [ 33 , 34 ]. The aforementioned nociceptive behaviours in rodents mimicked those experienced by people with migraine, who generally present with reduced involvement in routine physical activity and decreased interest in exploring new surroundings or objects during an acute migraine attack episode [ 34 , 35 ]. Therefore, we could use the parameters of the rat model to test antianalgesic drug potency.…”
Section: Discussionmentioning
confidence: 99%